Enhanced Bio-Oil Production from Agricultural Waste via NiCl₂-Assisted Pyrolysis: A Comparative Study of Candlenut and Coffee Shells - Yeni Ria Wulandari; Muhammad Arif Firmansyah; Yeni Variyana; Tri Haryono; Vinda Avri Sukma; Sudibyo Sudibyo; Nurjan Didik Purwanto (Chemistry Department, Faculty of Sciences and Mathematics, Diponegoro University, 2026)
Indonesia’s limited fossil fuel reserves, coupled with increasing national energy demand, highlight the need for alternative and renewable fuel sources. Biomass-derived bio-oil produced through pyrolysis represents a promising solution that can both reduce dependence on petroleum-based fuels and mitigate environmental pollution from underutilized biomass waste. This study investigates the production of bio-oil from candlenut shells and coffee shells through pyrolysis at varying temperatures (250, 350, and 450°C), conducted with and without a NiCl2 catalyst. The bio-oil was characterized for yield, density, and viscosity. The highest bio-oil yields from non-catalytic pyrolysis were achieved at 450°C, amounting to 39.14% for candlenut shells and 41.80% for coffee shells. Catalytic pyrolysis using NiCl2 enhanced the bio-oil yield, producing up to 55.78% (candlenut shells at 450°C) and 58.05% (coffee shells at 350°C). Density measurements showed the highest values in catalytic pyrolysis at 250°C, while the lowest densities were observed in non-catalytic pyrolysis at 450°C. Viscosity followed a similar trend, decreasing with increasing temperature and the presence of the catalyst. FTIR analysis confirmed the presence of functional groups including C–O, C=O, C=C, C≡C, C–H, and O–H. Overall, this study demonstrates the potential of candlenut and coffee shell waste as feasible feedstocks for bio-oil production, offering alternative renewable energy sources for future applications.